Enterovirus 71-Associated Infection in South Vietnam: Vaccination Is a Real Solution - Natalia I. Romanenkova; Thi Thanh Thao Nguyen; Liudmila N. Golitsyna; Natalia V. Ponomareva; Nadezhda R. Rozaeva; Olga I. Kanaeva; Artem V. Leonov; Nadezhda A. Novikova; Maina A. Bichurina (Vaccines, 2023)
Hand-foot-and-mouth disease (HFMD) is the most common enteroviral infection in South-East Asia. When evaluating the role of enterovirus 71 (EVA71) as an etiological agent of infectious disease in South Vietnam, we revealed a high proportion of EVA71 among identified species A enteroviruses found in 3542 samples from HFMD cases; 125 samples from cases of enteroviral meningitis; and 130 samples from acute flaccid paralysis (AFP) cases. These represent 50%, 54.8%, and 51.5%, respectively. According to molecular analysis, 90% of EVA71 were attributed to genotype C4 and 10% were attributed to genotype B5. The predominance of EVA71 circulation among the population proves the need to strengthen surveillance (with monitoring of enterovirus circulation for facilitation of HFMD outbreak prediction) and to increase the effectiveness of preventative measures by the implementation of vaccination against EVA71-associated infections. A phase III trial of a Taiwanese vaccine (EV71vac) in Taiwan and South Vietnam showed its safety, tolerability, and efficacy in children aged 2–71 months. This B4 genotype-based vaccine, which features cross-protection against B5 and C4 genotypes, and other existing EV71 vaccines can serve as a good approach to solving the HFMD problem, which is so important for Vietnam.